Concepciones formativas en programas de educación física en seis países de América Latina - Cunha de Paula, Sayonara; Ferreira Neto, Amarílio; Sarni, Mariana; dos Santos, Wagner (Universidad de Costa Rica, 2023)
The demands of globalization have had an impact on all parts of society and different reforms have been generated in Latin American higher education. The objective of the article was to analyze the organization of the training areas, the distribution of the subjects and the training conceptions of Study Programs of the Physical Education courses of six Latin American countries, namely, Argentina (5), Chile (12), Colombia (5), Mexico (3), Peru (2) and Uruguay (2). From a comparative design, it was characterized as a qualitative and exploratory research based on documentary analysis. The sources were composed of the Study Programs of 29 courses in force in 2020. The results identified 49 areas of training, with the subjects of the areas with the greatest offer being those that indicated the conceptions of Physical Education of the courses: in Argentina, the focus it was in sporting and biological aspects; in Chile, Peru and Uruguay the centrality of training was presented in the pedagogical aspects of Physical Education; in Colombia, there was a formative diversity (humanistic, biological, motor and sports); finally, in Mexico, the predominance was in training for sport. It is concluded that the diversity of training areas generates conceptual confusion in the field of Physical Education, which shows the need to establish a minimum standard for these Programs in the group of Latin American countries studied, in order to reduce the dissimilarity training in these contexts.